Gender Characterizations in Entrepreneurship: A Multi‐Level Investigation of Sex‐Role Stereotypes about High‐Growth, Commercial, and Social Entrepreneurs* - Gupta, Vishal K.; Wieland, Alice M.; Turban, Daniel B. (Journal of Small Business Management, 2019)
The purpose of this study is to cast new light on possible gender biases in implicit theories people hold about various forms of entrepreneurial activity. Using social role theory, we delve into sex‐role stereotypes associated with high‐ and low‐growth entrepreneurship and commercial and social entrepreneurship. Predictions were tested with an experimental design using both a between‐subject design to capture group‐level stereotypes and a within‐subject design to capture individual‐level stereotypes. Findings reveal that commercial and high‐growth entrepreneurs are perceived as more similar to men than to women and higher on agency than communality. Conversely, low‐growth entrepreneurs are perceived as more similar to women than men, and higher on communality than agency. Social entrepreneurs are uniquely perceived as similar to both men and women, though they are also considered higher on agency than communality. Interestingly, female, but not male respondents, perceive some overlap between the feminine gender role and high‐growth and commercial entrepreneurship. Notably, those higher on modern sexism perceive less overlap between entrepreneurship and femininity. Taken together, our results suggest that commercial high‐growth entrepreneurship is most strongly male‐typed, which is likely to be problematic for women (and non‐traditional men) wanting to start growth‐oriented ventures. Implications and directions for future research are discussed.
_eprint: https://www.tandfonline.com/doi/pdf/10.1111/jsbm.12495
Keywords: dept.mgt; peer-reviewed